Treatment of a mutant KRAS lung cancer cell line with polyisoprenylated cysteinyl amide inhibitors activates the MAPK pathway, inhibits cell migration and induces apoptosis. - Matthew D Gregory; Kweku Ofosu-Asante; Jassy Mary S Lazarte; Pablo E Puente; Nada Tawfeeq; Nadine Belony; Yong Huang; Ite A Offringa; Nazarius S Lamango (PLoS ONE)
KRAS mutations are the most common oncogenic mutations in lung adenocarcinoma in Black Americans. Polyisoprenylated Cysteinyl amide Inhibitors (PCAIs) constitute a group of potential cancer therapy agents that we designed to specifically disrupt and suppress hyperactive G-protein signaling, such as that caused by mutated RAS proteins. Here we determine the effects of PCAIs on the viability, G-protein levels, downstream mediators, and apoptosis-related proteins on the KRAS-mutated, Black American-derived lung adenocarcinoma cell line, NCI-H23. Of the 17 PCAIs tested, compounds NSL-YHJ-2-27 and NSL-YHJ-2-46 showed the most potency with EC50 values of 2.7 and 3.3 μM, respectively. Western blotting was used to determine the effect of the PCAIs on the phosphorylation levels of MAPK pathway enzymes. After 48 h exposure to 5 μM of the PCAIs, NSL-YHJ-2-46, the MAPK proteins BRAF, MEK1/2, ERK1/2, and p90RSK were activated through phosphorylation by 90, 190, 150 and 120%, respectively. However, CRAF/RAF1 phosphorylation decreased by 40%, suggesting significant changes in the KRAS/MAPK signaling patterns. Furthermore, 5 μM of NSL-YHJ-2-27 depleted the singly polyisoprenylated monomeric G-proteins RAC 1/2/3 and CDC42 by 77 and 76%, respectively. The depletion of these key cytoskeletal proteins may account for the observed inhibition of cell migration and invasion, and spheroid invasion observed on exposure to NSL-YHJ-2-27 and NSL-YHJ-2-46. Treatment with 5 μM of NSL-YHJ-2-27 suppressed full-length inactive caspase 3 and 7 levels by 72 and 91%, respectively. An analysis of cells treated with the fluorescently labeled active caspase 3/7 irreversible inhibitor, CaspaTagTM Caspase-3/7 in situ reagent revealed a 124% increase in active caspase at 3 μM over controls. These findings clearly show the direct effects of the PCAIs on the RAS signaling pathway. Given the profound increases observed in RPS6KA1/p90RSK phosphorylation, future work will involve a determination whether the proapoptotic isoforms of RPS6KA1/p90RSK are phosphorylated due to the PCAIs treatments. These results support the potential use of the PCAIs as targeted therapies against cancers with KRAS mutations.